Democracy without borders : transnationalization and conditionality in new democracies - Grugel, Jean (Routledge/ECPR studies in European political science, 1999)
This book carves out a new area of democratisation studies by analysing the transnational dimension and the role of non state actors across three different geographical regions. Chapters use data from Europe, Africa and Latin America.